Development of Media Branding on Batik Products for MSME Actors in Kulon Progo Regency - Istanti, Hanifah Nur; Kholifah, Nur; Putri, Gina Eka; Triyanto; Fitrihana, Noor (International Journal of Advanced Science Computing and Engineering, 2024)
Batik product marketing techniques are essential to the sustainability of an MSME in Kulon Progo. Various media can be used as a means of marketing. Based on previous research in 2021, the branding media used in the category is quite good, so there is a need to improve and develop the branding media used. This research aims to: (1) design the development of Sembung Batik branding media through an account on Shopee; and (2) Test the feasibility of developing Sembung Batik branding media through an account on Shopee. The research was carried out at Batik Sembung Kulon Progo. This type of research is development research using a 4D model and a quantitative descriptive approach. 4D Design comprises the definition, design, development, and dissemination stages. Three expert lecturers carried out the feasibility test. This research is to: (1). design the development of Sembung Batik branding media through an account on Shopee, which consists of four stages: the definition stage, the design stage, the development stage, and the disseminated stage, which is carried out 3 Shopee live times; and (2). the feasibility level of developing Sembung Batik branding media through an account on Shopee is very suitable for use based on the opinions of 3 experts. Based on this research, the development of branding media using live streaming can be implemented for other branding media so that it can have an impact on MSME branding.